The Latin New Testament: A Guide to its Early History, Texts, and Manuscripts - Houghton, H. A. G. (Oxford, UK Oxford University Press, 2017)
This book provides a comprehensive introduction to the history and development of the Latin New Testament and a user$1 (Bs guide to the resources available for research and further study. The first five chapters offer a new historical synthesis, bringing together evidence from Christian authors and biblical manuscripts from earliest times to the late Middle Ages. Each witness is considered in its chronological and geographical context, to build up the bigger picture of the transmission of the text. There are chapters introducing features of Latin biblical manuscripts and examining how the Latin tradition may serve as a witness for the Greek New Testament. In addition, each book of the New Testament is considered in turn, with details of the principal witnesses and features of particular textual interest. The three main scholarly editions of the Latin New Testament (the Vetus Latina edition, the Stuttgart Vulgate, and the Oxford Vulgate) are described in detail. Information is also given about other editions and resources, enabling researchers to understand the significance of different approaches and become aware of the latest developments. The Catalogue of Manuscripts gives full details of each manuscript used in the major editions, with bibliographical references and links to sets of digital images. The Appendices include concordances for the different ways in which manuscripts are cited in scholarly literature. An extensive reference bibliography of publications on the Latin New Testament is also supplied.s
English
Keywords: Literature: history & criticism; The Early Church; epistle; latin; vulgate; vetus latina; patristics; bible; manuscript; gospel; new testament; textual criticism; Jerome